2010
DOI: 10.1074/jbc.m110.115600
|View full text |Cite
|
Sign up to set email alerts
|

Role of CIC-5 in Renal Endocytosis Is Unique among CIC Exchangers and Does Not Require PY-motif-dependent Ubiquitylation

Abstract: Inactivation of the mainly endosomal 2Cl؊ /H ؉ -exchanger ClC-5 severely impairs endocytosis in renal proximal tubules and underlies the human kidney stone disorder Dent's disease. In heterologous expression systems, interaction of the E3 ubiquitin ligases WWP2 and Nedd4-2 with a "PY-motif" in the cytoplasmic C terminus of ClC-5 stimulates its internalization from the plasma membrane and may influence receptor-mediated endocytosis. We asked whether this interaction is relevant in vivo and generated mice in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 56 publications
2
52
0
Order By: Relevance
“…16 Morphologic analysis revealed a strong reduction of fluid-phase endocytosis in Rap DTubule and RapRic DTubule animals, whereas no change was observed in Ric DTubule mice (Figure 2A). Similarly, confocal microscopy analysis showed a reduced receptor-mediated endocytosis in Rap…”
Section: Loss Of Mtor In Pt Cells Results In a Fanconi-like Phenotypementioning
confidence: 99%
“…16 Morphologic analysis revealed a strong reduction of fluid-phase endocytosis in Rap DTubule and RapRic DTubule animals, whereas no change was observed in Ric DTubule mice (Figure 2A). Similarly, confocal microscopy analysis showed a reduced receptor-mediated endocytosis in Rap…”
Section: Loss Of Mtor In Pt Cells Results In a Fanconi-like Phenotypementioning
confidence: 99%
“…44 Immunoprecipitation AQP1-OKCs were resuspended in coimmunoprecipitation buffer(25 mM Tris-HCl, pH 7.6, 150 mM NaCl, 1% NP-40) supplemented with protease inhibitor cocktail (Roche Diagnostics), 1 mg/ml ubiquitin aldehyde, and 5 mM N-ethylmaleimide to limit protein degradation and deubiquitination as well as phosphatase inhibitors (100 mM NaF, 10 mM diNa-pyrophosphate, and 1 mM Na-orthovanadate). Insoluble material was removed, and 500 mg protein per sample was incubated with 4 mg rabbit IgG (The Jackson Laboratory) or polyclonal AQP1 at 4°C added with protein G Dynabeads (Invitrogen) for 4 hours.…”
Section: Antibodiesmentioning
confidence: 99%
“…For ClC-4, which has mostly been reported to localize to endosomes (4,27) but also to the endoplasmic reticulum (ER) (28), an N-terminal amino acid stretch is reportedly involved in ER retention when expressed heterologously (28). The predominantly endosomal ClC-5 (4, 27, 29 -32), a small portion of which is endogenously found also in the plasma membrane (30,33), bears a C-terminal-located PY motif (34). Although not required for in vivo ClC-5 function (33), studies in Xenopus oocytes and cultured opossum kidney cells revealed that ubiquitin ligases bind this motif and ubiquitylate ClC-5, stimulating its internalization from the cell surface (34,35).…”
mentioning
confidence: 99%
“…The predominantly endosomal ClC-5 (4, 27, 29 -32), a small portion of which is endogenously found also in the plasma membrane (30,33), bears a C-terminal-located PY motif (34). Although not required for in vivo ClC-5 function (33), studies in Xenopus oocytes and cultured opossum kidney cells revealed that ubiquitin ligases bind this motif and ubiquitylate ClC-5, stimulating its internalization from the cell surface (34,35). Although endogenous ClC-6 localizes to late endosomes (36), heterologously expressed ClC-6 has been found on early and recycling endosomes (37).…”
mentioning
confidence: 99%